Improving the quality characteristics of abrasive water jet machining of marble material using multi-objective artificial bee colony algorithm - Pawar, Padmakar J.; Vidhate, Umesh S.; Khalkar, Mangesh Y. (Journal of computational design and engineering, 2018)
Graphical abstract Graphical Abstract AbstractAlthough abrasive water jet machining has proved its capabilities for cutting marble material in a most economic and environment friendly manner, is facing serious issues related to dimensional inaccuracy and striation marks. This has put limit on its applications. Also, due to complex nature of abrasive water jet machining process, it is very difficult to control all three quality factors i.e. kerf taper, kerf width, striation marks simultaneously to achieve desired quality. This work therefore deals with multi-objective optimization considering three objectives as: minimization of kerf width, minimization of kerf taper, and maximization of depth of striation free surface in abrasive water jet machining process. The response surface modeling is used to establish the relation between various input parameters such as stand of distance, traverse speed, water pressure, and abrasive flow rate, with objectives mentioned above. Application of well-known meta-heuristics named artificial bee colony algorithm is extended to multi-objective optimization with posteriori approach by incorporating the concept of non-dominated sorting. Set of Pareto optimal solutions obtained by this proposed approach provides a ready reference for selecting most appropriate parameter setting on the machine with respect to objectives considered in this work. Highlights Provides methodology to concurrently minimize the dimensional inaccuracy along with striation marks for cutting marble material with abrasive water jet machining process.Application of artificial bee colony algorithm is extended to multi-objective optimization.The set of Pareto-optimal solution obtained using proposed approach can be used as a ready reference by the process engineers for cutting marble material by AWJM process.